Myocardial Remodeling in Early Chronic Kidney Disease—Mineral and Bone Disorder Model with Low Bone Turnover - Bogdanova, Evdokia; Sadykov, Airat; Ivanova, Galina; Zubina, Irina; Beresneva, Olga; Galkina, Olga; Parastaeva, Marina; Sharoyko, Vladimir; Dobronravov, Vladimir (Kidney and dialysis, 2023)
Chronic kidney disease—mineral and bone disorder (CKD-MBD) plays a significant role in causing cardiovascular morbidity and mortality related to CKD. CKD-MBD has been studied during advanced stages when changes in inorganic phosphate (Pi) and its hormonal regulation are obvious. The initial phases of myocardial remodeling (MR) in early CKD-MBD remain poorly understood. We induced mild CKD-MBD in spontaneously hypertensive rats using 3/4 nephrectomy. Animals were fed standard chow, containing 0.6% phosphate. In each animal, we analyzed indices of chronic kidney injury, bone turnover and Pi exchange, and assessed the myocardial histology and gene expression profile. Applied CKD-MBD models corresponded to human CKD S1-2 with low bone turnover and without an increase in systemic Pi-regulating factors (parathyroid hormone and fibroblast growth factor 23). In mild CKD-MBD models, we found MR features characterized by cardiomyocyte hypertrophy, interstitial and perivascular fibrosis, intramyocardial artery media thickening, along with alterations in Ppp3ca, Mapk1, Jag1, Hes1, Ptch1, Numb, Lgr4 and Bmp4 genes. Among other genes, the down-regulation of Jag1 was most tightly associated with either myocardial hypertrophy or fibrosis. Myocardial alterations concurrently occurred with mild CKD-MBD and comprised fibrosis preceding cardiomyocyte hypertrophy. The histological features of MR were associated with myocardial P accumulation in settings of low bone turnover, prior to a response of systemic Pi-regulating factors and with alterations in calcineurin, ERK1/2, Notch, BMP and Hedgehog genes.